The Influence of Restaurant Location on Customer Satisfaction and Business Profit: A Case Study in South Tangerang and Bintaro - Fajar SM Harahap (Publikasi Indonesia, 2026)
The culinary industry in urban areas such as Bintaro and South Tangerang is highly competitive, where location selection is a key determinant of restaurant business success. The background of this study is based on the importance of strategic location not only in attracting customers but also in improving operational efficiency and business profitability. This study aims to analyze the effect of restaurant location on customer satisfaction and business profit and to test the mediating role of customer satisfaction in this relationship. The research method uses a quantitative approach with a survey technique. Data were collected through questionnaires distributed to 100 respondents consisting of customers and restaurant managers in the Bintaro area. Data analysis was conducted using descriptive statistics, Pearson correlation, simple linear regression, and path analysis with the assistance of SPSS software. The results show that restaurant location has a positive and significant effect on customer satisfaction ( ; ) and business profit ( ; ). Furthermore, customer satisfaction acts as a mediating variable that strengthens the relationship between location and profit, with an indirect effect of 0.47. The most influential location factors are accessibility, parking availability, and restaurant visibility from the main road. The study concludes that a strategic location is a critical determinant of restaurant success, both directly and through enhanced customer satisfaction. These findings contribute theoretically to the development of location–performance models in the culinary business context and provide practical implications for entrepreneurs and area developers in location-based planning and decision-making.